2020
DOI: 10.1016/j.rmcr.2019.100967
|View full text |Cite
|
Sign up to set email alerts
|

Long-term responsiveness to mepolizumab after failure of omalizumab and bronchial thermoplasty: Two triple-switch case reports

Abstract: Severe asthma affects between 5 and 10% of patients with asthma worldwide and requires best standard therapies at maximal doses. A subgroup of patients remains refractory to all treatments. We describe two case reports with severe allergic asthma who progressively worsened over the years despite the best therapy. The patients were first treated with omalizumab, which was completely ineffective, and then with bronchial thermoplasty (BT), again without clinical benefit. Since our patients met the AIFA criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…A multicentre clinical trial (OSMO) demonstrated switching to an anti-eosinophil biologic in asthmatic patients was safe and efficacious in improving asthma control, healthcare utilization and exacerbations, even without an omalizumab washout period [ 50 ]. In several other case series, patients with severe allergic asthma demonstrated improved symptom control and a reduction in asthma exacerbations and severity after switching from omalizumab to mepolizumab [ 101 ]. As biologics target different inflammatory receptors and cytokines, patients with a suboptimal response to omalizumab might benefit from an anti-eosinophil agent, depending on their treatable traits.…”
Section: Discussionmentioning
confidence: 99%
“…A multicentre clinical trial (OSMO) demonstrated switching to an anti-eosinophil biologic in asthmatic patients was safe and efficacious in improving asthma control, healthcare utilization and exacerbations, even without an omalizumab washout period [ 50 ]. In several other case series, patients with severe allergic asthma demonstrated improved symptom control and a reduction in asthma exacerbations and severity after switching from omalizumab to mepolizumab [ 101 ]. As biologics target different inflammatory receptors and cytokines, patients with a suboptimal response to omalizumab might benefit from an anti-eosinophil agent, depending on their treatable traits.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a small number of case reports describing successful switching between biologics in severe asthma patients have been published 40‐43 . These reports mainly included patients eligible for both anti‐IgE and anti‐IL‐5 treatments and, due to the different time points these biologics became available to the market, they mainly describe alterations from omalizumab to mepolizumab 40,41 from omalizumab to benralizumab, 42 and from mepolizumab to benralizumab 43 .…”
Section: How Should Switching Been Performedmentioning
confidence: 99%
“…Recently, a small number of case reports describing successful switching between biologics in severe asthma patients have been published 40‐43 . These reports mainly included patients eligible for both anti‐IgE and anti‐IL‐5 treatments and, due to the different time points these biologics became available to the market, they mainly describe alterations from omalizumab to mepolizumab 40,41 from omalizumab to benralizumab, 42 and from mepolizumab to benralizumab 43 . The results of a recent post hoc meta‐analysis of pooled data from ‘Mepolizumab as Adjunctive Therapy in Patients with Severe Asthma’, (MENSA) 44 and’Mepolizumab adjUnctive therapy in subjects with Severe eosinophilic Asthma’ (MUSCA) 45 studies indicate that mepolizumab reduced exacerbation frequency and improved HRQoL and asthma control in patients with severe eosinophilic asthma, irrespective of prior omalizumab use 46 .…”
Section: How Should Switching Been Performedmentioning
confidence: 99%
“…Severe asthma is defined as asthma that remains uncontrolled despite treatment with high‐dose inhaled corticosteroids (ICS) and long‐acting ÎČ2‐agonists 1 . Bronchial thermoplasty (BT) can control severe asthma by reducing the amount of smooth muscle in the bronchial wall 2,3 . Furthermore, several clinical studies have shown that biological treatments, such as humanized monoclonal antibody against IL‐5 receptor α (benralizumab), humanized antibody against IL‐4Rα (dupilumab), and humanized monoclonal antibody against interleukin‐5 (IL‐5) (mepolizumab) are effective in severe asthma 1 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 Bronchial thermoplasty (BT) can control severe asthma by reducing the amount of smooth muscle in the bronchial wall. 2 , 3 Furthermore, several clinical studies have shown that biological treatments, such as humanized monoclonal antibody against IL‐5 receptor α (benralizumab), humanized antibody against IL‐4Rα (dupilumab), and humanized monoclonal antibody against interleukin‐5 (IL‐5) (mepolizumab) are effective in severe asthma. 1 Tezepelumab is a human IgG2 monoclonal antibody that inhibits thymic stromal lymphopoietin (TSLP).…”
Section: Introductionmentioning
confidence: 99%